L'Isola che (non) c'è La letteratura russa per l'infanzia in Italia (1945-1991) - DE FLORIO, GIULIA (Biblioteca di Studi Slavistici, 2022)
This volume presents a survey of Russian children's literature published in Italy from 1945 to 1991. On the one hand the analysis accounts for the historical, social and literary context of post-war Italy, in which the books were published. On the other, a textual and translating analysis of a selection of volumes is conducted within the theoretical framework of Translation Studies and Adaptation Studies. The book aims at: filling a gap in Slavic studies, which so far have dealt discontinuously with children's literature; including Russian children's literature in the history of Italian publishing; providing some preliminary observations regarding the image of Russian children's literature created in Italy from the post-war period to the collapse of the USSR.